2023
DOI: 10.3390/molecules28041819
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Pump (QacA, QacB, and QacC) and β-Lactamase Inhibitors? An Evaluation of 1,8-Naphthyridines against Staphylococcus aureus Strains

Abstract: The bacterial species Staphylococcus aureus presents a variety of resistance mechanisms, among which the expression of β-lactamases and efflux pumps stand out for providing a significant degree of resistance to clinically relevant antibiotics. The 1,8-naphthyridines are nitrogen heterocycles with a broad spectrum of biological activities and, as such, are promising research targets. However, the potential roles of these compounds on bacterial resistance management remain to be better investigated. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…However, previous studies have shown that interior membrane transporter actively capture drugs and exclude them out [22] . Therefore, the active efflux system also plays a certain role in the mechanism of bacterial resistance to β-lactam drugs, especially the ABC transports [23] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, previous studies have shown that interior membrane transporter actively capture drugs and exclude them out [22] . Therefore, the active efflux system also plays a certain role in the mechanism of bacterial resistance to β-lactam drugs, especially the ABC transports [23] .…”
Section: Discussionmentioning
confidence: 98%
“…Due to the poor permeability of the bacterial intima to β-lactams, these tend to accumulate in the Intermembrane space and act on the target proteins. However, previous studies have shown that interior membrane transporter actively capture drugs and exclude them out [22] . Therefore, the active efflux system also plays a certain role in the mechanism of bacterial resistance to β-lactam drugs, especially the ABC transports [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, evaluation of the 1,8-naphthyridine sulfonamides showed that they could inhibit both β-lactamases and the QacC and QacA/B efflux pumps in S. aureus [101]. Thus, these agents and their derivatives show promise in addressing infection by pathogens by targeting more than one resistance mechanism, as in the case of resistances conferred by enzymatic inactivation and active drug efflux.…”
Section: Efflux Pump Inhibitionmentioning
confidence: 99%